Long noncoding RNAs: a potential novel class of cancer biomarkers - Yarmishyn, Aliaksandr A.; Kurochkin, Igor V. (Frontiers in Genetics, 2015)
Long noncoding RNAs (lncRNAs) are a novel class of RNA molecules defined as transcripts longer than 200 nucleotides that lack protein coding potential. They constitute a major, but still poorly characterized part of human transcriptome, however, evidence is growing that they are important regulatory molecules involved in various cellular processes. It is becoming increasingly clear that many lncRNAs are deregulated in cancer and some of them can be important drivers of malignant transformation. On the one hand, some lncRNAs can have highly specific expression in particular types of cancer making them a promising tool for diagnosis. The expression of other lncRNAs can correlate with different pathophysiological features of tumor growth and with patient survival, thus making them convenient biomarkers for prognosis. In this review we outline the current state of knowledge about the fast growing field of application of lncRNAs as tumor biomarkers.